METHODS FOR CLEANING DUST IN THE AIR FILTER - Igamberdiev Anvarjon Uktamovich (Bright Mind Publishing, 2025)
The article presents several types of airborne dust collection systems that are an important part of industry. They are designed to clean and filter air before it is released into the environment or the workplace.
Keywords: Dust collection system, cleaning equipment, dust filter, centrifugal fans, dust collection device.